Quantitative on‐line concentration for capillary electrophoresis with inkjet sample introduction technique. Issue 15 (19th June 2015) - Rang, Ying; Zeng, Hulie; Nakajima, Hizuru; Kato, Shungo; Uchiyama, Katsumi
<x xml:space="preserve">Abstract</x> A quantitative sample introduction method based upon inkjet injection was applied to capillary electrophoresis coupled with stacking and sweeping on‐line concentration techniques. Methylxanthines were used as model compounds for the proof‐of‐concept of the method. The volume of injected sample could be easily manipulated by controlling the number of ejected droplets in the injection procedure. Under optimized conditions, a linear relationship between the ejected droplet number and peak area was obtained when the droplet number introduced into the capillary was less than 100. Under optimized quantitative on‐line concentration conditions, the limits of detection for theobromine, caffeine, and theophylline were 1.0, 2.0, and 1.0 μM, respectively. The inkjet injection system was evaluated by comparing it with conventional injection methods. The electropherogram of the inkjet injection mode was the same as that for hydrodynamic injection mode, and no sample discrimination was observed compared with the electrokinetic injection mode. The established method was applied to the determination of methylxanthines in bottled green tea. The recoveries of theobromine, caffeine, and theophylline were 94.1, 110.6, and 86.8%, respectively. We conclude that proposed method can be used for quantitative concentration for capillary electrophoresis, thus resulting in an improved accuracy.